Product placement and its legal aspects - Korčeková, Andrea (2010)
The thesis deals with analysis of legal aspects of product placement. First, it looks at product placement from a general point of view. The work explains past legal framework where product placement was a part of "unfair competition" both in EU and Czech Republic. Then, it analyzes particular articles of directive 2007/65/EC which regulates the term product placement as the first in the history. The analyses showed that there are a lot of vague and disputable terms, e. g. "significant value", provision "free of charge", or ensuring that viewers are "clearly informed" about existence of product placement. Further, the work analyzes an implementation of the directive to the czech law and its comparison with Slovakia. Product placement was translated into czech law as "umístění produktu". The implementation is reflected in the "on-demand audiovisual media services Act" but also in the amendment of Act Nr. 231/2001 Sb. By contrast, Slovakia did not create a new special Act for non-linear audiovisual media services, just amended Act Nr. 308/2000 Z.z. and some other affecting laws. Finally, the work confronts the legal theory with praxis. This is done by a survey. The most important result of the survey showed that almost a half of the respondents think that product placement is not a commercial practice. This fact highlights the importance of ensuring that viewers are "clearly informed" about the existence of product placement and also the provision of consumer protection.